KINERJA PENCAHAYAAN ALAMI PADA RUANG KELAS DI BANGUNAN BERTINGKAT MENENGAH TERHADAP VARIASI WINDOW TO WALL RATIO DAN KONDISI PENGHALANG EKSTERNAL - A'yun, Qurrotul; Shafa, Nadila Hanindia; Putri, Faizah Azalia (EMARA: Indonesian Journal of Architecture, 2025)
Daylighting plays a critical role in classroom design due to its impact on visual comfort, occupants’ health, and building energy efficiency. In mid-rise buildings located in tropical climates, increasing window area is often implemented without adequate consideration of surrounding environmental conditions, which may result in excessive illuminance and visual discomfort. This study aims to analyze the daylighting performance of mid-rise classroom buildings in relation to window-to-wall ratio (WWR) variations and external obstruction conditions. The study employed daylight simulation using Velux Daylight Visualizer with three WWR configurations: 25%, 37%, and 50%. Simulations were conducted at 09:00, 12:00, and 15:00 in December to represent tropical daylight conditions. The analysis focused on average illuminance values measured on a working plane at a height of 0.75 m above the floor, under both unobstructed and externally obstructed conditions. The simulation results indicate that increasing WWR significantly raises indoor illuminance levels. Under unobstructed conditions, WWRs of 37% and 50% produced high average daily illuminance values of 2,079.9 lux and 2,582.6 lux, respectively, indicating a potential risk of overlighting. In contrast, under external obstruction conditions, average illuminance values across all WWR variations ranged from 752.8 to 842.9 lux and exhibited more stable daylight distribution. This study concludes that a WWR of 37% provides the most balanced daylighting performance by ensuring sufficient natural light while minimizing the risk of visual discomfort, particularly in mid-rise classroom buildings within dense tropical urban environments. The findings offer practical insights for designing classroom openings by integrating window proportion and external environmental context.